SOME DATA ON THE HYDROCHEMICAL REGIME AND PRIMARY PRODUCTION IN NORWEGIAN SEA (Nekotorye Dannye o Gidrokhimicheskom Rezhime i Pervichnoi Produktsii Norvezhskogo Morya) - Zlobin,V. S.; Sapronetskaya,N. G.; Alekseeva,A. G. (1970)
Data on the content of biogenic components in the sea, their distribution pattern and seasonal variations in concentrations are of great significance not only for the evaluation of primary production in various water masses but also for forecasting the production of a given sea region. Of special significance is phosphorous which occurs in albumin and phytoplankton cells which are rich in the energy of functional groups. This paper discusses the results of studying the pattern of seasonal distribution of phosphorous and the correlations between some of the biogenic elements and physical-chemical factors. (Author) Trans. of Polyarnyi Nauchno-Issledovatelskii Institut Morskogo Rybnogo Khozyaistva i Okeanografii. Nauchno-Tekhnicheskii Byulleten (USSR) n11 p133-144 1968, by M. Slessers.